A STUDY OF MACRO FACTORS INFLUENCING HAPPINESS INDEX OF EASTERN EUROPEAN COUNTRIES - Dave, Maulik; Dave, Tejas; Parwani, Ashwin; Rami, Ashish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Happiness has been of importance for individuals, organisations and even for the nations primarily due to its influence on productivity and prosperity of the respective entities. There are plethora of micro and macro factors affecting happiness. This research study aims to investigate the association of macro factors viz. gross domestic product and per capita gross domestic product with happiness level and the extent to which they exercise their influence on happiness.Gross domestic product, per capita gross domestic product and happiness index of east European countries have been examined. Various statistical techniques including multiple regression equation have been used to analyze the data, The study revealed that per capita gross domestic product is an important variable influencing happiness index of a nation signaling that any government trying to achieve higher happiness index will have to pay adequate attention to per capita gross domestic product.